Re-Emergent Inhibition of Cochlear Inner Hair Cells in a Mouse Model of Hearing Loss - Zachary, Stephen Paul (J Neurosci, 2015)
Hearing loss among the elderly correlates with diminished social, mental, and physical health. Age-related cochlear cell death does occur, but growing anatomical evidence suggests that synaptic rearrangements on sensory hair cells also contribute to auditory functional decline. Here we present voltage-clamp recordings from inner hair cells of the C57BL/6J mouse model of age-related hearing loss, which reveal that cholinergic synaptic inputs re-emerge during aging. These efferents are functionally inhibitory, using the same ionic mechanisms as do efferent contacts present transiently before the developmental onset of hearing. The strength of efferent inhibition of inner hair cells increases with hearing threshold elevation. These data indicate that the aged cochlea regains features of the developing cochlea and that efferent inhibition of the primary receptors of the auditory system re-emerges with hearing impairment. SIGNIFICANCE STATEMENT Synaptic changes in the auditory periphery are increasingly recognized as important factors in hearing loss. To date, anatomical work has described the loss of afferent contacts from cochlear hair cells. However, relatively little is known about the efferent innervation of the cochlea during hearing loss. We performed intracellular recordings from mouse inner hair cells across the lifespan and show that efferent innervation of inner hair cells arises in parallel with the loss of afferent contacts and elevated hearing threshold during aging. These efferent neurons inhibit inner hair cells, raising the possibility that they play a role in the progression of age-related hearing loss.